(untitled) (Research, Society and Development, 2021)
Introduction: The theme involving mental health has been widely discussed in recent years, thus awakening this phenomenon to the context of Higher Education, specifically to university students of the nursing course, since the academic routine involving studies of theory and professional practice of this is surrounded by ambiguous experiences, thus causing these students high levels of stress and anxiety. Objectives: to smooth the mental health of university students of the nursing course through a literature review, seeking to identify the main mental illnesses faced by nursing students in undergraduate studies and discuss actions to protect and promote mental health in nursing university students. Methods: This is a qualitative and descriptive research, developed through an integrative literature review (ILR), through lilacs, MEDLINE, SCIELO databases, and studies from 2011 to June 2021 were selected, with descriptors: Mental Health; Anxiety; Stress; Pandemic Covid-19; Health strategies; University Students and Nursing. Results: Among the 9 articles investigated, published in 2021, reactions such as increased stress, anxiety, decreased sleep quality, fear associated with decreased performance were generally due to the absence of a daily routine and the many hours invested in social/digital media. Conclusion: Mental health is an aspect that should be treated as one of the pillars for the teaching-learning process of nursing students, since their role of caring is essential to always remain on a balance basis.